Improving Reading Comprehension Skill through the School Literacy Movement for Children with Learning Difficulties - Kemala Viyana; Asep Bayu Dani Nandiyanto; Tedi Kurniawan; Muhammad Roil Bilad (Universitas Pendidikan Indonesia (UPI), 2023)
One of the obstacles faced by children with learning difficulties is the low level of reading comprehension. This problem was found in elementary school, Indonesia, children who have learning difficulties have a low level of understanding. The purpose of this study was to determine the effect of the school literacy movement in improving the reading comprehension skills of children with learning difficulties. The method in this study using quantitative research. From the results, there are still some students who do not know the school literacy movement. Students' understanding of the literacy movement towards reading texts can be improved by providing interesting and illustrated reading texts online using the Zoom Meeting application with educators. The results of the research showed that the post-test value was 61.9% greater than the pre-test value of 47.6%, so the difference was 14.3%. Therefore, we can improve students' reading comprehension skills in school literacy activities.